1982
DOI: 10.1093/schbul/8.3.504
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Family Attitudes About Schizophrenia: Implications for Genetic Counseling

Abstract: Psychiatrists are giving increased attention to genetic counseling for mental illness. However, the burden of these illnesses are perceived by families and the degree to which families feel a need for genetic counseling have yet to be established. Attitudes and perceptions measured in this study focus on etiology, familial risk, and socioeconomic burden of schizophrenia, as well as childbearing plans and the acceptability of genetic counseling. Members of 17 families, each with a child diagnosed schizophrenic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0
1

Year Published

1984
1984
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 13 publications
5
21
0
1
Order By: Relevance
“…Particularly important is the motivation to bear children and reproductive intentions. These variables have been found to have a significant influence on outcomes of genetic counseling (Sorenson et al, 1984) and also on perception of recurrence risks (Schulz, 1982). The expected correlation is negative: the higher the motivation the lower the perceived risk.…”
Section: Risk Perception In Genetic Counselingmentioning
confidence: 99%
“…Particularly important is the motivation to bear children and reproductive intentions. These variables have been found to have a significant influence on outcomes of genetic counseling (Sorenson et al, 1984) and also on perception of recurrence risks (Schulz, 1982). The expected correlation is negative: the higher the motivation the lower the perceived risk.…”
Section: Risk Perception In Genetic Counselingmentioning
confidence: 99%
“…Two early reports suggested that individuals affected with psychiatric illness may underestimate illness risk in their offspring. In a survey of patients with schizophrenia, Schulz and colleagues 29 reported that 58% estimated the risk of the illness in their offspring at less than 9%. In contrast, siblings of these patients tended to overestimate risks for their own children.…”
Section: The Potential Role Of Genetic Counseling In Psychiatrymentioning
confidence: 99%
“…Despite the existence of a substantial literature concerning public attitudes toward mental illness, there has been relatively little research assessing public knowledge of mental illness in general -of its symptoms, causes, and treatments. Investigations of knowledge about schizophrenia, specifically, are even more rare and have focused mainly on mental health professionals (Gallagher, 1977;Soskis, 1972) and on families with schizophrenic members (Hatfield, 1978;Schulz et al, 1982).…”
Section: George Mason Universitymentioning
confidence: 99%